Fruit flies of Batu Timbang Forest Within Imbak Canyon Conservation Area, Sabah, Malaysia (Diptera: Tephritidae) - Rahman, Homathevi (Journal of Tropical Biology & Conservation (JTBC), 2019)
A survey of fruit fly fauna was carried out at Batu Timbang Research Station, (Imbak Canyon Conservation Area – ICCA), Telupid, Sabah from 17th to 20th of August 2017. Fruit flies were collected using aerial net and bottle traps containing an attractant (Methyl Eugenol (ME) and Cue-lure (CUE)) at Lanap Trail, Rafflesia Trail and base camp. A total of 77 fruit flies belonging to Bactrocera were collected. This includes six species and three morphospecies, of which Bactrocera tau was the dominant species (56 individuals). This is the first study on fruit fly species at Imbak Canyon Conservation Area.